Proposal of an ontology based web search engine - Deco, Claudia (2008)
When users search for information in a web site, sometimes they do not get what they want. Assuming that the scope where the search take place works fine, there are some problems caused by the way the user interact with the system, others that refer to characteristics of the language used, and others caused by the lack or nonexistent semantics in web documents. In this work, we propose a web search engine of a particular web site that uses ontologies and information retrieval techniques. Although the architecture we propose is applicable to any domain, the experimentation was done in a tourism web site. The results show a substantial improvement in the effectiveness of the search, with a gain of 33% in Precision.